2014
DOI: 10.1105/tpc.114.125591
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHROME INTERACTING FACTOR1 Enhances the E3 Ligase Activity of CONSTITUTIVE PHOTOMORPHOGENIC1 to Synergistically Repress Photomorphogenesis in Arabidopsis    

Abstract: CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1) is a RING/WD40 repeat-containing ubiquitin E3 ligase that is conserved from plants to humans. COP1 forms complexes with SUPPRESSOR OF PHYTOCHROME A (SPA) proteins, and these complexes degrade positively acting transcription factors in the dark to repress photomorphogenesis. Phytochrome-interacting basic helixloop-helix transcription factors (PIFs) also repress photomorphogenesis in the dark. In response to light, the phytochrome family of sensory photoreceptors simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 67 publications
5
98
0
Order By: Relevance
“…3a-c). PIF1 also displayed interaction with COP1 in the dark as previously shown 7 . However, these assays showed that CUL4, COP1 and SPA1 interacted preferentially with a slow migrating form of PIF1 in response to light ( Fig.…”
Section: Cop1supporting
confidence: 79%
See 4 more Smart Citations
“…3a-c). PIF1 also displayed interaction with COP1 in the dark as previously shown 7 . However, these assays showed that CUL4, COP1 and SPA1 interacted preferentially with a slow migrating form of PIF1 in response to light ( Fig.…”
Section: Cop1supporting
confidence: 79%
“…Because PIF1 formed a complex with COP1 and SPA1, components of the E3 ubiquitin ligases in the dark 7 , we examined whether the CUL4 COP1-SPA E3 ubiquitin ligases also play a role in the light-induced degradation of PIF1 in Arabidopsis. We performed immunoblots for PIF1 levels in the individual components of the CUL4 COP1-SPA complex mutants both in the dark and light.…”
Section: Cop1mentioning
confidence: 99%
See 3 more Smart Citations